MAPPING A THEORETICAL FRAMEWORK FOR ORCIT - Carsten, Svetlana (Vertimo studijos, 2017)
The ORCIT project (Online Resources for Conference Interpreter Training) was launched in September 2010 and is currently in its sixth successive year. ORCIT is a multilingual and interactive learning resource with a designated website (www.orcit.eu) which offers pedagogical best practice in interpreter training. Focus of the modular resources is on six main competences necessary for successful training: listening and analysis; mastery of the mother tongue and public speaking; early and advanced consecutive interpreting; early and advanced simultaneous and research skills. In ORCIT, we are near the stage where the corpus of material is substantial enough to subject it to empirical evaluation. Extra funding is currently being sought to launch evaluation in October 2016. By definition, in any learning environment, including a technology-enhanced environment, the overall goal for both the student and the teacher is to expand and consolidate the student’s knowledge of the subject and to improve performance. Therefore the aim of an evaluation of ORCIT would be to assess the use of the resources in a blended learning environment. A proposed theoretical framework which could provide a suitable platform for an experimental design is Diana Laurillard’s the Conversational Framework and a classification of five media forms (Laurillard 1993 & 2002). Relevance of the Conversational Framework and five media forms to ORCIT are the subject of the discussion in this paper. The focus is on the media forms which would assist in the evaluation design.